2017
DOI: 10.1111/iju.13419
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in the etiology and management of vesicovaginal fistula

Abstract: Vesicovaginal fistula has remained a scourge and of public health importance, causing significant morbidity, and psychological and social problems to the patient. Continuous wetness, odor and discomfort cause serious social issues. The diagnosis has been traditionally based on clinical evaluation, dye testing, cystoscopic examination and contrast studies. A successful repair of such fistulas requires an accurate diagnosis and timely surgical intervention using techniques that are based on basic surgical princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 32 publications
1
57
0
7
Order By: Relevance
“…It occurs especially in women living in the remote rural areas of Pakistan. In our study, we found that 75% patients were residents of rural areas as reported by other 3,5,11 studies. This sad reflection of low socio economical aspect is seen all over the developing world, as 60-70 percent of patients were residents of rural areas in different studies.…”
Section: Methodssupporting
confidence: 87%
“…It occurs especially in women living in the remote rural areas of Pakistan. In our study, we found that 75% patients were residents of rural areas as reported by other 3,5,11 studies. This sad reflection of low socio economical aspect is seen all over the developing world, as 60-70 percent of patients were residents of rural areas in different studies.…”
Section: Methodssupporting
confidence: 87%
“…In addition, postvoid residuals were lower than 50 mL in all patients. one side and vaginal flora on the other [17][18][19]. As we already mentioned, in Western countries, the majority of VVFs are commonly associated with iatrogenic injury that comes about during gynecological surgery, mainly hysterectomy [20,21].…”
Section: Resultsmentioning
confidence: 96%
“…Traditional teaching typically dictates waiting at least three months after childbirth before surgically repairing a fistula to allow time for healing and inflammation to subside as well as recovery from central necrosis, edema, or infection. 4,7,11 Additionally, conservative management for women who present within the first three months for repair may help the fistula spontaneously close. 4 However, some experts would argue, that it is reasonable to repair before the 3-month mark so long as the fistula tract is mature and the tissue appears healthy.…”
Section: Discussionmentioning
confidence: 99%